A review of the article globalization and culture: Four paradigmatic views by Kavous Ardalan - Suhada, Suhada (Indonesian Journal of Business, Accounting and Management, 2024)
Recovery Version (See for detail) This essay offers a thorough analytical assessment of Kavous Ardalan's paradigmatic framework on the relationship between globalization and culture. From universalist interpretations of global uniformity to context-specific studies of cultural adaptation and critical evaluations of ideological and structural domination, each paradigm presents a unique worldview. The review points out that the interpretive paradigm emphasises local agency, meaning-making, and the cultural distinctiveness of globalisation, whereas the functionalist paradigm stresses technical determinism and systemic order. The radical structuralist and radical humanist viewpoints, on the other hand, show how globalisation exacerbates class struggle and ideological control. The paper argues that no single view can fully convey the complexity of the cultural effects of globalization by combining several paradigms. Instead, it moves from universalist interpretations of global uniformity to context-specific studies of cultural adaptation and critical assessments of ideological and structural domination. Each paradigm presents a unique worldview. The review points out that the interpretive paradigm emphasises local agency, meaning-making, and the cultural distinctiveness of globalisation, whereas the functionalist paradigm stresses technical determinism and systemic order.